Placental chemical elements concentration in small fetuses and its relationship with Doppler markers of placental function. (July 2021) - Gómez-Roig, MD; Mazarico, E.; Cuadras, D.; Muniesa, M.; Pascal, R.; Ferrer, P.; Cantallops, M.; Arraez, M.; Gratacós, E.; Falcon, M.
Abstract: Introduction: In this study, we aimed at quantifying placental concentrations of 22 chemical elements in small fetuses (SGA) as compared with normally grown fetuses (AGA), and to assess the relationship with Doppler markers of placental function. Methods: Prospective cohort study, including 71 SGA fetuses (estimated fetal weight < 10th percentile) and 96 AGA fetuses (estimated fetal weight > 10th percentile), recruited in the third trimester of gestation. The placental concentration of 22 chemical elements was determined by inductively coupled plasma optical emission spectrophotometer (ICP-OES, ICAP 6500 Duo Thermo): aluminum (Al), beryllium (Be), bismuth (Bi), calcium (Ca), cadmium (Cd), cobalt (Co), chrome (Cr), copper (Cu), magnesium (Mg), manganese (Mn), molybdenum (Mo), nickel (Ni), phosphorus (P), lead (Pb), rubidium (Rb), sulfur (S), strontium (Sr), titanium (Ti), thallium (Tl), antimony (Sb), selenium (Se), and zinc (Zn). Placental function was assessed by measuring the following fetal-maternal parameters: Uterine artery Pulsatility Index (UtA PI), Umbilical artery Pulsatility Index (UA PI) and Middle Cerebral artery Pulsatility Index (MCA PI). The association between the chemical elements concentration and study group and the association with Doppler measures were evaluated. Results: SGA was associated with significantly (p < 0.05) lower concentrations of Al (AGA 21.14 vs SGA 0.51 mg/kg), Cr (AGA 0.17 vs SGA 0.12 mg/kg), Cu (AGA 0.89 vs SGA 0.81 mg/kg), Mg (AGA 0.007 vs SGA 0.006 g/100g), Mn (AGA 0.60 vs SGA 0.47 mg/kg), Rb (AGA 1.68 vs SGA 1.47 mg/kg), Se (AGA 0.02 vs SGA 0.01 mg/kg), Ti (AGA 0.75 vs SGA 0.05 mg/kg) and Zn (AGA 9.04 vs SGA 8.22 mg/kg). Lower placental concentrations of Al, Cr, Mn, Se, Ti were associated with abnormal UtA, UA and MCA Doppler. Discussion: Lower placental concentrations of Al, Cr, Cu, Mn, Rb, Se, Ti and Zn are associated with SGA fetuses and abnormal fetal-maternal Doppler results. Additional studies are required to further understand how chemical elements affect fetal growth and potentially find strategies to prevent SGA. Highlights: This study aims to assess the relationship between metal concentrations in the placenta and its function. Lower placental concentrations of Al, Cr, Cu, Mg, Mn, Rb, Se, Ti and Zn are related to SGA. Lower placenta concentrations of Al, Cr, Mn, Se, Ti correlates to abnormal fetal-maternal Doppler.